Analysis on the Light-Scattering Effect in Dye-Sensitized Solar Cell according to the TiO2 Structural Differences - Min-Kyu Son; Hyunwoong Seo; Soo-Kyoung Kim; Na-Yeong Hong; Byung-Man Kim; Songyi Park; Kandasamy Prabakar; Hee-Je Kim (International Journal of Photoenergy)
A light-scattering layer is widely used in highly efficient dye-sensitized solar cells (DSCs) because it improves the light-harvesting ability of a DSC by reflecting the light passing through the transparent TiO2 layer. Among many parameters affecting this light-scattering effect, the thickness of the TiO2 photoelectrode is also a significant parameter. However, most studies regarding the influence of the TiO2 photoelectrode thickness on the light-scattering effect have only focused on the thickness of the transparent TiO2 layer and have ignored the light-scattering layer thickness itself. Therefore, in this study, we analyzed the light scattering effect according to the thickness of the light-scattering layer and the resulting photovoltaic performance of the DSC. Finally, it was confirmed that the light-scattering effect is enhanced to some degree with the increase of the light-scattering layer thickness, while it is weakened when the light-scattering layer thickness is further increased.